Lecture 15. Chemical Equilibrium, Part II - Donald R. Blake (University of California Irvine (UCI), 2013)
(en)UCI Chem 1B is the second quarter of General Chemistry and covers the following topics: properties of gases, liquids, solids; changes of state; properties of solutions; stoichiometry; thermochemistry; and thermodynamics. Index of Topics: 0:00:28 Reaction Quotient 0:02:25 Writing Equilibrium Constants 0:09:55 Equilibrium Concentrations for the Reaction 0:16:54 Equilibrium Constant Kp 0:20:58 Free Energy vs Progress of Reaction 0:22:36 Equilibrium Constant and Free Energy 0:23:56 Equilibrium 0:24:40 Reaction Quotient 0:28:47 Equilibria Involving Condensed Phases 0:29:43 Vapor Color Intensity 0:31:21 Consider the Following Equilibrium. 0:36:52 Adding Equilibrium Reactions 0:41:40 Writing Equilibrium Constants 0:43:10 Chemical Kinetics and Chemical Equilibrium 0:45:31 Summary of Concepts 0:46:44 Multiple Equilibria 0:47:03 Carbonic Acid Ionizes in Water 0:49:19 Dr. Hess Returns 0:54:11 Reverse Equation 1 and Multiply by Two 0:56:28 Methane and Water 0:59:12 Isomerization Equilibrium Constant